2002
DOI: 10.1038/sj.ejcn.1601372
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of measured sleeping metabolic rate and predicted basal metabolic rate during the first year of life: evidence of a bias changing with increasing metabolic rate

Abstract: Objective: To compare measurements of sleeping metabolic rate (SMR) in infancy with predicted basal metabolic rate (BMR) estimated by the equations of Schofield. Methods: Some 104 serial measurements of SMR by indirect calorimetry were performed in 43 healthy infants at 1.5, 3, 6, 9 and 12 months of age. Predicted BMR was calculated using the weight only (BMR-wo) and weight and height (BMR-wh) equations of Schofield for 0 -3-y-olds. Measured SMR values were compared with both predictive values by means of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…In infants, sleeping energy expenditure is used as a proxy for REE due to the practical considerations of measuring energy expenditure in this age group. 24 The metabolic cart measures infant respiratory gas exchange of oxygen consumption (VO 2 ) and carbon dioxide production (VCO 2 ) in 1-minute intervals. The initial period of infant adjustment and any period of significant movement that altered REE were extracted prior to analysis.…”
Section: Anthropometric Measurementsmentioning
confidence: 99%
“…In infants, sleeping energy expenditure is used as a proxy for REE due to the practical considerations of measuring energy expenditure in this age group. 24 The metabolic cart measures infant respiratory gas exchange of oxygen consumption (VO 2 ) and carbon dioxide production (VCO 2 ) in 1-minute intervals. The initial period of infant adjustment and any period of significant movement that altered REE were extracted prior to analysis.…”
Section: Anthropometric Measurementsmentioning
confidence: 99%
“…By the age of 1 year, the growth rate constant sharply (by more than one order of magnitude) decreases and becomes 0.3. At the same time, the basal metabolic rate at the age of 1 year reaches the highest values [31,32]. Spe cial calculations [33] showed that the actual expenses for the syntheses associated with the growth processes even in the first 3 months of life, when the growth rate of the child is maximum, are not more than 20 kcal/day, that is 7-8% of the basal metabolism or 2-3% of the daily energy expenditure of the body.…”
Section: Causes Of Age Related Changes In Energy Metabolismmentioning
confidence: 87%
“…Then, the intensity of energy metabolism stabilizes at a level characteristic of adults. Long term observa tions showed that all these changes are observed in both boys and girls, but in girls they occur, an average, 0.5-1 year earlier [32]. Thus, the facts testify to the reciprocal relationships between the intensity of met abolic and growth processes [37]-exactly the oppo site conclusion as compared to the widespread and seemingly obvious point of view.…”
Section: Relationships Between Energy and Growth Processesmentioning
confidence: 97%
See 1 more Smart Citation
“…These differences contribute to the quality loss of diet or physical exercise programs, which may be harmful to the population's health. The inadequation of the BEE estimation equations for specific populations, such as the Brazilian and Australian ones, ends up bringing dissatisfaction and discredit to the given services besides disturbing their aims, as weight body composition control [9][10][11][12][13][14][15] . The aim of this study was to compare the results of the BEE estimated by mathematical equations proposed by Harris-Benedict …”
Section: Introductionmentioning
confidence: 99%